Peran dan Daya Saing Sektor Pertanian dan Pariwisata dalam Pembangunan Wilayah Kabupaten Gianyar - I GUSTI AYU ARI JULIA MALINI; MADE ANTARA; DEWA MADE RAKA SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
Role and Competitiveness of Agriculture and Tourism Sectors in the Development of Gianyar Regency In plain view, it can be assumed that the wheels of the economy in the Gianyar regency are driven by the synergy between the agricultural sector, the tourism sector including the socio-cultural aspects that support tourism. This research aims to understand the role of the agricultural sector and the tourism sector in the regency’s economy, which sector is the dominant one and the competitiveness of each sector in the development of the regency. This research uses descriptive analysis method, location quotient (LQ), dynamic location quotient (DLQ) approach, combined analysis of LQ and DLQ and differential shift from shift share analysis approach. The analysis suggests that the contribution of the agricultural sector to the regency’s economy quantitatively decreased from the beginning to the end of the study period. In contrast, the economic contribution of the tourism sector in the regency have increased. This study suggests that Gianyar has six sectors that have the potential to become leading sectors in the future, two sectors that are presently leading and possibly will still lead in the future, eight prospective sectors, four mainstay sectors and three lagging sectors. On this study period that is between 2014-2018, the agricultural sector shows weak competitiveness, while the tourism sector shows strong competitiveness.